Critical Historiographical Analysis of Philip K. Hitti’s History of The Arabs: An Examination of Positionalism and Arab Historical Narratives: Analisis Historiografi Kritis terhadap History of The Arabs karya Philip K. Hitti: Telaah atas Posisionalitas dan Narasi Sejarah Arab - Zulkifli, Muh; Anggariani, Dewi; Pababbari, Musafir (The Department of Islamic History and Culture in cooperation with the Center for Islamic History and Culture in Aceh and Malay World Studies (PUSAKA), Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia, 2026)
Philip K. Hitti's History of the Arabs (1937) is a canonical work that shaped the Western understanding of Arab history. This article presents a historiographical critique of the text using Edward Said's Orientalism, Michel-Rolph Trouillot's concept of silencing, and Chase F. Robinson's study of Islamic historiography. The analysis reveals that while Hitti's work aimed to reclaim Arab history from Orientalist bias, it remained trapped within the same discursive logic. Its